Characterization of post‐ictal clinical signs in dogs with idiopathic epilepsy: A questionnaire‐based study - Aran Nagendran; Julie A. Nettifee; Dani Carter; Karen R. Muñana (Journal of Veterinary Internal Medicine)
Abstract Background Post‐ictal (PI) clinical signs are a key defining stage of seizure manifestation in dogs. However, this phase remains poorly understood. Objectives To further characterize PI signs and their relation to other parts of a seizure, and understand the owner's perception of how PI signs affect the quality of life (QOL) of the dog. Animals Eight‐seven dogs with a diagnosis of idiopathic epilepsy from a single institution. Methods The prospective questionnaire‐based study surveying owners of dogs previously and newly diagnosed with idiopathic epilepsy. Results Post‐ictal signs were identified in 79/87 dogs, 5/5 of dogs with focal seizures and 74/82 of dogs with generalized seizures. Median duration of PI signs was 30 minutes (range, 5‐4320 minutes). The most common PI signs reported were disorientation (50/79) and wobbliness or clumsiness (49/79). Within a year, a change in PI signs was seen in 18/79 dogs. The administration of benzodiazepines was significantly associated with an increase in duration of PI signs (P = .04). Post‐ictal signs had more impact on dogs' quality of life compared with ictal signs (P < .01). Groupings of co‐existing PI signs identified included disorientation, blindness and deafness. Conclusion Post‐ictal signs are a commonly reported aspect of seizures in dogs with idiopathic epilepsy, both in focal as well as generalized seizures. Co‐existence of signs could provide some valuable insight into the relevance of this particular phase of a seizure. Owner‐reported signs and documentation emphasize the need for a better understanding of PI signs in dogs with idiopathic epilepsy.